Enhanced Isolation of Streptomyces from Different Soil Habitats in Calamba City, Laguna, Philippines using a Modified Integrated Approach - Jhon Wilson A. Antido; Fresthel Monica M. Climacosa (International Journal of Microbiology)
Streptomyces species are considered to be the most prolific sources of various bioactive secondary metabolites that are important for antibiotic production. Here, we describe a modified integrated approach to isolate Streptomyces species from diverse soil habitats, such as dumpsite, garden, forest, grassland, and riverside in Calamba City, Laguna, Philippines. A total of 25 soil samples were collected from a depth of 0–20 cm using systematic random soil sampling. All soil samples were air-dried, crushed, pretreated with calcium carbonate, and incubated on a rotary shaker. Isolation of Streptomyces in soil samples was then performed using the standard serial dilution plate technique on starch casein agar supplemented with nystatin (50 μg/ml) and ampicillin (5 μg/ml). Identification of the Streptomyces isolates was done using a polyphasic method that includes morphological and biochemical characterization. A total of 103 morphologically and biochemically distinct Streptomyces were isolated from diverse soil habitats. The number of Streptomyces isolates varied in each collection site, with the highest number collected from dumpsite soil and the least from forest soil. Most of the hydrogen sulfide producers were noted to be isolated from dumpsite samples. Moreover, more Streptomyces were isolated in soil habitats at higher altitudes with a slightly acidic to alkaline pH and a temperature ranging from 29 to 33°C. Employing the modified integrated approach, we have isolated up to 10 times more Streptomyces compared to early studies. These Streptomyces isolates can be valuable for future drug discovery and development research.